Forest Management Units As A Manager Of Watershed Management (Implementation Of One Watershed, One Plan, One Manager) - Supriatna, Agus; Rachman, Hardina Arisa Alvia; Hakim, Azis (Mutiara: Multidiciplinary Scientifict Journal, 2024)
Watershed management is very important because there is a decrease in the quality of the environment in the watershed. Current problems in watershed management are due to the existence of an egosectoral, not yet integrated and the absence of institutions that specifically and intensely manage watersheds from upstream to downstream well through community empowerment programs and soil and water conservation activities. Forest Management Units as a site-level organization is present as a solution to the problem of watershed management by becoming a watershed manager. The watershed manager functions to coordinate, manage, and manage, together with other stakeholders to achieve watershed management objectives.